2014
DOI: 10.1007/s10661-014-3812-8
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient dynamics and seasonal variation of phytoplankton assemblages in the coastal waters of southwest Bay of Bengal

Abstract: In order to understand the phytoplankton community structure and its relationship with the environmental variables in the near shore waters of Kalpakkam, east coast of India, observations were carried out during 2008-2009. Phytoplankton population was comprised of 219 species, and the density was higher during the southwest monsoon (SWM) and inter-monsoon seasons than that of north east monsoon (NEM) season. The nutrient status on a temporal and spatial scale indicated the impact of point sources carrying anth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 34 publications
2
14
1
Order By: Relevance
“…Similar type of upsurge in relative dominance of diatom followed by dinoflagellates has been observed in coastal waters of south- western BoB associated with lower saline conditions (Rajasekar et al 2010). In agreement to the present observation, recent study at south-west coastal waters of BoB has resulted with similar species richness of 219 taxa predominated by diatoms followed by dinoflagllates (Achary et al 2014). The high species richness and ubiquity of diatoms indicated a healthy ecosystem in coastal waters of north-western BoB (Armbrust 2009).…”
Section: Spatial and Seasonal Distribution Of Zooplanktonsupporting
confidence: 91%
“…Similar type of upsurge in relative dominance of diatom followed by dinoflagellates has been observed in coastal waters of south- western BoB associated with lower saline conditions (Rajasekar et al 2010). In agreement to the present observation, recent study at south-west coastal waters of BoB has resulted with similar species richness of 219 taxa predominated by diatoms followed by dinoflagllates (Achary et al 2014). The high species richness and ubiquity of diatoms indicated a healthy ecosystem in coastal waters of north-western BoB (Armbrust 2009).…”
Section: Spatial and Seasonal Distribution Of Zooplanktonsupporting
confidence: 91%
“…Islam and Aziz (1975) and Aziz and Islam (1979) reported 64 marine phytoplankton species and 22 marine dinoflagellates species from the north-eastern Bay of Bengal, respectively that was nearly similar with the findings of this study. However, Achary et al (2014) reported 219 marine phytoplankton species in Bacillariophyta, Cyanophyta and Dinophyta group from the coastal waters of southwest Bay of Bengal that was different from the current study. This might be varied because of seasonal differences since Achary et al ( 2014) collected samples for one year covering all seasons.…”
Section: Phytoplankton Identificationcontrasting
confidence: 99%
“…Globally, many studies have been conducted to determine phytoplankton compositions, abundances, distribution and diversity in different seas (e.g., Eker-Develi and Kideys, 2003;Guo et al, 2014;Ismael, 2015;Polikarpov et al, 2016;etc.). Some studies are also conducted in the vicinity of the Bay of Bengal, however, most of them are focused on Indian coastal waters (e.g., Sarojini and Sarma, 2001;Madhav and Kondalarao, 2004;Achary et al, 2014;Baliarsingh et al, 2016;etc. ) Islam and Aziz (1975) and Aziz and Islam (1979) assessed the marine phytoplankton distribution in the north-eastern Bay of Bengal of Bangladesh, but it was very fragmented that needs to be updated.…”
Section: Introductionmentioning
confidence: 99%
“…Low N:P supply ratios may result in a significant shift in the phytoplankton assemblage to a community dominated by N-fixing cyanobacteria and a supply of atmospheric N 2 estimated to be up to 60% of total supply (Vrede et al, 2009). Achary et al (2014) reported that the comparison of ambient nutrient ratios with the Redfield ratio (N/P =16:1) showed a clear temporal variation in the factors that regulate the phytoplankton 0 1 2 3 S1 S2 S3 S4 S5 S6 S7 S8 S9 S10 S11 S12 S13 S14 S15 growth. The dry season was evident to have an acute N-limitation for algal growth whereas P-limitation was encountered during the wet season.…”
Section: Nutrients Parametersmentioning
confidence: 99%